2009
DOI: 10.3844/ajas.2009.523.528
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Volatile Compounds from Genus Ocimum

Abstract: There are distinct varieties of basil types in the genus Ocimum which makes them very special. Genus Ocimum is widespread over Asia, Africa and Central & Southern America. All basils are member of the Lamiaceae family. The colors of the leaves vary from bright green to purple-green and sometimes almost black. Fresh basil leaves have a strong and characteristic aroma, not comparable to any other spice, although there is a hint of clove traceable. Ocimum Sanctum, also addressed as Ocimum Tenuiflorum is a sacred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…This clearly indicated the absorption potential of the molecule against UV-B radiation and their possible adaptabilities. The chemical composition of basil oil obtained in the present study is in agreement with the earlier findings of Kumar et al (2009), reporting eugenol as a main compound of essential oil produced from a local variety of O. sanctum L. Mondal et al (2007) also reported essential oil with similar chemical composition having eugenol (57.9%), b-caryophyllene (15.3%), germacrene-D (9.1%) and b-elemene (7.6%) as major chemical constituents in fresh leaves of O. sanctum L. However, our results showed some variations with earlier studies related to its major compound (Vani et al 2009). Zheljazkov et al (2008) have reported methyl chavicol, eugenol, and eucalyptol, as the main constituents of holy basil of local varieties in Mississippi.…”
Section: Discussioncontrasting
confidence: 77%
“…This clearly indicated the absorption potential of the molecule against UV-B radiation and their possible adaptabilities. The chemical composition of basil oil obtained in the present study is in agreement with the earlier findings of Kumar et al (2009), reporting eugenol as a main compound of essential oil produced from a local variety of O. sanctum L. Mondal et al (2007) also reported essential oil with similar chemical composition having eugenol (57.9%), b-caryophyllene (15.3%), germacrene-D (9.1%) and b-elemene (7.6%) as major chemical constituents in fresh leaves of O. sanctum L. However, our results showed some variations with earlier studies related to its major compound (Vani et al 2009). Zheljazkov et al (2008) have reported methyl chavicol, eugenol, and eucalyptol, as the main constituents of holy basil of local varieties in Mississippi.…”
Section: Discussioncontrasting
confidence: 77%
“…The genus Ocimum consists of about 200 species of shrubs and herbs, and a few of them are being cultivated all around the world, as a natural herbal medicine . Basil has been used as a culinary herb since prehistoric times, and its essential oils have been employed in food, flavor, and fragrance for cosmetic industries …”
Section: Introductionmentioning
confidence: 99%
“…However, chemical compositions of genus Ocimum are reported to contain linalool, linuleic acid, p-cymene, estragosl, eucalyptol, eugenol, citral, thujone, ocimene, camphor, methyl chavicol, oleic acid, and many terpenes (Watson and Preedy 2008). Similarly, Vani et al (2009) reported the two important volatile compounds (i.e., eugenol and methyl chavicol) in O. sanctum and O. bacillicum. They reported that O. bacillicum collected from Malysia at the temperature 27.3 ‱ C was rich in methyl chavicol.…”
Section: Antibacterial Activity Against Waterborne Pathogensmentioning
confidence: 95%